Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Campaign against the Vice President and General Prosecutor of the Russian Federation; press conference of centrist parties. Featured in the program: Khasbulatov, Ruslan Imranovich (Chairman of the Supreme Soviet of the Russian Federation); Stepankov, Valentin Georgievich (Chief State Prosecutor of the Russian Federation); Rutskoi, Aleksandr Vladimirovich (Vice President of the Russian Federation) Contributors: Berdnikova, Nina (Anchor) Series description: A program about the activity of the Supreme Soviet of the Russian Federation. Кампания против вице-президента и Генерального прокурора России; пресс-конференция центристских партий. В программе участвуют: Хасбулатов, Руслан Имранович (Председатель Верховного Совета Российской Федерации); Степанков, Валентин Георгиевич (Генеральный прокурор Российской Федерации); Руцкой, Александр Владимирович (Вице-президент Российской Федерации) Создатели: Бердникова, Нина (Ведущий/Ведущая) Описание серии: Передача о деятельности Верховного Совета Российской Федерации.